Indications for an inducible component of error-prone DNA repair in yeast. - Siede, W. (Nature Publishing Group, 1984)
In a thermoconditional mutant of mutagenic DNA repair (rev 2ts = rad 5-8) of Saccharomyces cerevisiae recovery of survival and mutation frequencies can be monitored by incubating UV-irradiated cells in growth medium at a permissive temperature (23 degrees C) before plating and a shift to restrictive temperature (36 degrees C). Inhibition of protein synthesis with cycloheximide during incubation at permissive conditions blocks this REV 2 dependent recovery process in stationary phase rev 2ts cells, whereas it can be reduced but not totally abolished in exponentially growing cells. These results indicate a strict dependence on post-irradiation protein synthesis in stationary phase cells and argue for a considerable constitutive level and only limited inducibility in logarithmic phase cells. The UV inducibility of the REV 2 coded function in stationary phase cells could be confirmed by analysis of the dose-response pattern of the his 5-2 reversion: in stationary phase rev 2ts cells, the quadratic component of the biphasic linear-quadratic induction kinetics found at 23 degrees C, which is interpreted as the consequence of induction of mutagenic repair, is eliminated at 36 degrees C.